SHALAHUDDIN AL-'Aá¸ŒLABI Analisis Metodologi Kritik Matan HadÄ«á¹¡ Terhadap Riwayat Yang Bertentangan Dengan Akal, Indra dan Sejarah - Muhammad Nabat Ardli; Reza Hilmy Luayyin (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
Research on HadÄ«á¹¡ cannot be separated from two main elements, called sanad and matan. Among HadÄ«á¹¡ scholars, research on sanad receives more attention than matan, which prompted Salahuddin al-'Aá¸labi to write the book "Manhaj Naqd al-Matn 'Ind Ulama al-Hadits al-Nabawiâ€, which specifically discusses the critique of HadÄ«á¹¡ texts. Among several of his critical methodologies are critiques of the matan through rational, sensory, and historical approaches. This research uses descriptive analysis with a normative approach. The results of the analysis show that 1) Al-'Aá¸labi's critical methodology towards HadÄ«á¹¡ texts that contradict Reason, Senses, and History employs several methods and approaches including hierarchical and integrative assumptions, as well as synchronization methods. 2) Some of Al-'Aá¸labi's assumptions employ a hierarchical approach, where each assumption cannot be separated from the Qur'an and HadÄ«á¹¡, reason, then senses, and followed by history. The hierarchical assumptions made can be done not necessarily in a structured (systematic) way but can be done randomly as long as the Qur'an and HadÄ«á¹¡ remain the top priority in building assumptions. Al-'Aá¸labi's assumptions also use an integrative approach where his assumptions are built and mutually supported among various elements to produce a higher norm. 3) A variety of methods employed by Al-'Aá¸labi with rational, sensory, and historical approaches use synchronization methods. The synchronization method referred to is when there is a contradiction in understanding the HadÄ«á¹¡ text.